Public perceptions and aesthetic preferences of lakeshore landscape: the example of Lake Velence (Hungary) - Cai, Xuecheng; Boromisza, Zsombor (Acta Geographica Debrecina Landscape & Environment series, 2020)
Earlier, intervention programs and tourism development projects in the lakeside area of Lake Velence have led to the diversification of lakeshore landscape and shoreline. In the current study, we investigated the public aesthetic preferences of varying lakeshore landscapes, driving factors (which cause preference deviation and visual discomfort), and judgments of perceived beauty of 14 lakeshore scenes. The study also examined the differences in preferences of lakeshore landscapes between experts and waterfront residents. The results indicated that landscape characteristic and maintenance state have a significant impact on the receptor’s preference. In the investigation of lakeside landscape preference with different natural degrees, both the near-natural lakeshore and the natural lakeshore are lacking attention and attraction. Though natural (“wild”) lakeshore beneficial to the birds and other wildlife, overgrown riparian / aquatic plants and rigid shoreline caused visual fatigue and boredom feel. These findings provide a reference for the forthcoming lakeside intervention projects and land-use decisions.